Sustainability and determinants of Italian public deficits before and after Maastricht - Emma Galli; Fabio Padovano (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper has two goals. 1) To evaluate the sustainability of Italian public deficits according to the methodology developed by Trehan and Walsh (1988, 1991) and Bohn (2004); 2) To analyze how the determinants of debt creation evolved in the years following the Maastricht Treaty and how this evolution shaped the development of the Italian public finances. The analysis is carried out in three steps; first we estimate and compare the stochastic properties of the main indicators of the Italian budget performance to test for sustainability; second, we confront the results of a cointegration-vector error correction model on two sample periods: a ?pre Maastricht? (1950-1991) and a ?post Maastricht? (1950-2002), to identify the main determinants of public deficits, according to the theoretical literature and the dynamic relationship between each of them and the dependent variable; third, we use the results of these estimates to specify a dummy variable model that evaluates how Italian fiscal policy reacted to changes in these determinants in the 1950-2002 sample. We conclude that a) In this period Italian public finances failed the sustainability test; b) Debt creation is much more sensitive now than before 1991 to external constraints, chiefly the numerical rules imposed by the Maastricht Treaty itself, institutional factors, such as the budget approval rules and the relative political power of the Minister for the Economy.
Keywords: H62; E62; 330; public deficits; Maastricht Treaty; comparative test; cointegration; Haushaltsdefizit; Finanzpolitik; Konvergenzkriterien; Schätzung; Italien